2020
DOI: 10.1186/s12882-020-02101-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D and FGF23 with serum ferritin in hypoparathyroid thalassemia: a case control study

Abstract: Background FGF23 controls serum l,25(OH)2D3 levels and phosphate homeostasis. This study evaluates the effects of ferritin on intact PTH, FGF23, and l,25(OH)2D3 in patients with major thalassemia. It also evaluates FGF23 changes in patients with hypoparathyroidism to clarify the interaction between FGF23 and PTH in the absence of proper PTH functioning in human. Methods In this case-control study, 25 major-beta thalassemia patients with hypoparathy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…3 B), thus agreeing with our hypothesis that the increased FGF-23 level might be a compensatory response to iron overload in thalassemia. The present finding was consistent with the previous reports of the elevated level of FGF-23 in thalassemia being associated with iron utilization 48 , 49 . For instance, Saki et al 49 demonstrated in β-thalassemia major patients a positive correlation between serum FGF-23 and ferritin from iron overload.…”
Section: Discussionsupporting
confidence: 94%
“…3 B), thus agreeing with our hypothesis that the increased FGF-23 level might be a compensatory response to iron overload in thalassemia. The present finding was consistent with the previous reports of the elevated level of FGF-23 in thalassemia being associated with iron utilization 48 , 49 . For instance, Saki et al 49 demonstrated in β-thalassemia major patients a positive correlation between serum FGF-23 and ferritin from iron overload.…”
Section: Discussionsupporting
confidence: 94%
“…Iron accumulation in parathyroids and insufficient treatment with iron chelation agents are associated with the development of HPT in β-thalassemia patients [64]. Based on data collected from a group of patients with β-thalassemia major, Saki et al found a strong correlation between 1,25(OH)2D3, FGF23, and ferritin levels [105]. In addition, in the study of De Sanctis et al, approximately half of the patients (48.9%) with β-thalassemia (major or intermedia) and hypoparathyroidism had a serum ferritin level over 2500 ng/mL [64].…”
Section: Parathyroid Dysfunctionmentioning
confidence: 99%
“…In BTH patients with hypoparathyroidism, serum ferritin might act as a stimulator of Fibroblast Growth Factor 23 which controls the serum levels of 1,25-dihydroxyvitamin D3 values [ 58 ]. Anomalies of klotho were suggested as well, but there is still a gap in terms of clinical evidence [ 59 ].…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%